Historiographical and Archaeological Study of the M.S. Thomson Collection at the Milwaukee Public Museum - (:unkn) unknown (My University, 2014)
This thesis is a historiographical and archaeological study of artifacts collected by avocational archaeologist M.S. Thomson, focusing on sites in and near the Sheboygan Marsh, Wisconsin. Evidence from this indicates continuous occupation beginning as early as 12,000 years ago. The history of the acquisition of the collection by the Milwaukee Public Museum is summarized and a comprehensive description of the various kinds of materials in the collection is provided. The locations of sites where Thomson collected are mapped and then compared to other known collectors' assemblages from the area. These other known sites were documented as part of the Great Lakes Archaeological Research Center's Sheboygan Marsh Project (1990 to 1993) that included interviews with local collectors. In the process, ten of the sites where Thomson collected were found to not yet be codified, therefore inventory forms for these sites were submitted to the Wisconsin Historical Society. Additionally, the lithics in the collection indicate a strong Late Paleoindian component at some of these sites. The information I was able to gather from this collection speaks to its potential as a research tool as well as for education.
Keywords: Avocational; Collector; Donation